A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species - Ando, Kiyoshi; Ruzzier, Enrico (Zootaxa, 2017)
The genus Euhemicera Ando, 1996 (Tenebrionidae: Cnodalonini) is recorded from Myanmar for the first time. The newly identified representatives of this genus are described herein as Euhemicera amicorum sp. n.. An updated species catalogue of Euhemicera with distributional data is provided. Currently, one hundred species are known to represent this genus. Available data reveals that Euhemicera is widely distributed throughout the oriental region, with the highest diversity in South East Asia.